Optimized simultaneous saccharification and co-fermentation of rice straw for ethanol production by Saccharomyces cerevisiae and Scheffersomyces stipitis co-culture using design of experiments - Suriyachai, Nopparat; Weerasaia, Khatiya; Laosiripojana, Navadol; Champreda, Verawat; Unrean, Pornkamol (Bioresource technology, 2013)
•Co-culture SSCF process of rice straw for ethanol production was optimized.•Effect of solid loading on enzyme hydrolysis was examined.•Co-culture was systematically optimized using design of experiment (DoE) approach.•Highly efficient and scalable SSCF by co-culture yielded 99% of theoretical yield.•Maximum ethanol concentration achieved by co-culture SSCF process was 28.6g/L. Herein an ethanol production process from rice straw was optimized. Simultaneous saccharification and co-fermentation (SSCF) using Saccharomyces cerevisiae and Scheffersomyces stipitis co-culture was carried out to enhance ethanol production. The optimal saccharification solid loading was 5%. Key fermentation parameters for co-culture including cell ratio, agitation rate and temperature was rationally optimized using design of experiment (DoE). Optimized co-culture conditions for maximum ethanol production efficiency were at S. cerevisiae:S. stipitis cell ratio of 0.31, agitation rate of 116rpm and temperature of 33.1°C. The optimized SSCF process reached ethanol titer of 15.2g/L and ethanol yield of 99% of theoretical yield, consistent with the DoE model prediction. Moreover, SSCF process under high biomass concentration resulted in high ethanol concentration of 28.6g/L. This work suggests the efficiency and scalability of the developed SSCF process which could provide an important basis for the economic feasibility of ethanol production from lignocelluloses.